The benefit of the glassy state of reinforcing particles for the densification of aluminum matrix composites - Kvashnin, Vyacheslav I.; Dudina, Dina V.; Ukhina, Arina V.; Koga, Guilherme Yuuki; Georgarakis, Konstantinos (MDPI, 2022)
In metallic glass-reinforced metal matrix composites, the glassy phase can serve a dual purpose: (i) it can behave as soft binder and porosity remover during consolidation; and (ii) it can act as the hard reinforcing phase after densification. The present work aimed to demonstrate the benefit of the glassy reinforcing particles for the densification of aluminum matrix composites. The consolidation behavior of Al–50 vol.% Fe-based alloy mixtures prepared using a glassy Fe66Cr10Nb5B19 alloy powder (Tg = 521 °C, Tx = 573 °C) or a crystalline Fe62Cr10Nb12B16 alloy powder was studied under spark plasma sintering (SPS) and hot pressing (HP) conditions. The powders were consolidated by heating above the glass transition temperature of the glassy alloy (up to 540 °C in SPS and 570 °C in HP). When the coarse aluminum powder was used, the reinforcing particles formed chains within the microstructure. In composites formed from the fine Al powder, the particles of the Fe-based alloy were separated from each other by the metallic matrix, and the tendency to form agglomerates was reduced. The glassy state of the alloy was shown to be beneficial for densification, as the metallic glass acted as a soft binder. The densification enhancement effect was more pronounced in the case of reinforcing particles forming chains. The hardness of the Al–50 vol.% glassy Fe66Cr10Nb5B19 composites obtained by SPS was twice the hardness of the unreinforced sintered aluminum (110 HV1 versus 45 HV1).
Keywords: aluminum matrix composite; spark plasma sintering; hot pressing; microstructure; metallic glass; reinforcement